Changes in Soil Physicochemical and Water Properties in Response to Exotic Acacia Invasion in a Bornean Coastal Heath Forest - Mohamad Hilmi, Ibrahim; Rahayu Sukmaria, Sukri; Kushan U., Tennakoon; Nurul Naqibah, Rosli; Faizah, Metali (Springer Nature Switzerland AG, 2023)
This study investigates the impacts of Acacia invasion on Bornean heath forest (HF) soils. Soil profiles and water properties at one soil depth (< 1 m) and physicochemical properties with Soil Fertility Index(SFI) and Soil Evaluation Factor (SEF) from the topsoil or three soil depths of Acacia-invaded and non-invaded HF were assessed. Acacia invasion modified soil profiles by producing thicker horizons O and B but waning horizon E. Thick leaf litter layer in invaded HF was associated with a significant decrease in soil bulk density, moisture, organic matter (OM), total organic carbon, water volume, and NH4+ but a significant increase in soil temperature, and soil water pH, NO3− and PO43−. A significant increase in soil pHwater and available P were observed across all depths, except for topsoil exchangeable NH4+. Acacia invasion significantly reduced total acidity and base cations across soil depths, and total N and exchangeable H, NO3−, Mg, and Al at certain depths, implying leaching and reduced acidification. Topsoil SFI and SEF of Acacia-invaded HF were significantly lower than non-invaded HF, possibly due to slower decomposition rates resulting in lower OM and base concentrations. Variations in topsoil physicochemical properties generated two distinct clusters with the Acacia-invaded plots strongly influenced by PC1 (exchangeable soil NH4+ and temperature), while the non-invaded plots were strongly influenced by PC2 (pHKCl, total acidity, exchangeable Ca, H, and Al). Acacia invasion negatively impacted soil properties, potentially affecting plant, soil, and microbial communities, thus indicating that invasion mitigation and ecological restoration efforts should be prioritized for the invaded HF.